Exact dynamic analysis of multi-segment cable systems. (1st January 2021) - Fei, Han; Zichen, Deng; Danhui, Dan
Highlights: An exact method for dynamic analysis of multi-segment cable systems is proposed. Consider multiple effects such as flexural stiffness, sag, and elastic supports simultaneously. The closed-formed frequency equation of the system is obtained. The accuracy of the method has been verified by the full scaled real cable test. Abstract: Cable-supported structure is a common system widely used in engineering, with the rapid development of the infrastructure and transportation industry, its structural form has become more and more complicated. Multi-segment cable system, which consists of a suspension cable and several lateral supports, such as the cable-damper system, the main cable of a suspension bridge, etc., is one of the important cable support systems. Due to the low structural rigidity and damping, its dynamic problems have always been the focus of engineering. To obtain a more general conclusion, a unified dynamic model considering the effect of cable sag, additional cable force, flexural stiffness, and the support stiffness of lateral components are considered in this paper for the first time. However, the exact analysis of this model is difficult, in view of this, the dynamic stiffness method is employed in this paper to investigate the dynamic characteristic of the multi-segment cable system. The accuracy of the proposed method is verified by comparing with finite element solutions and experimental results. Results show that the position of lateral supports has a strong coupling effect and influence the lower-order mode more significantly than higher-order modes, and the maximum frequency value can be reached by installing the supports equidistantly.